Factors affecting seabird abundance and interaction with the nearshore 'for hire' recreational charter fishery in New South Wales, Australia. Issue 2 (25th January 2022) - Hughes, Julian M.; Johnson, Daniel D.; Collins, Damian; Ochwada‐Doyle, Faith A.; Murphy, Jeffrey J.
Abstract: Bycatch in fishing gear is a threat to the conservation of seabird populations globally. Factors affecting interactions with commercial fisheries are well documented; however, little comparable information exists for recreational fisheries. High participation rates in many recreational fisheries globally mean that interactions with seabirds may have population‐level impacts. This study specifically assessed factors affecting seabird interactions with a recreational hook‐and‐line fishery in New South Wales (NSW), Australia. Observers on 'for hire' nearshore charter vessels collected data on seabird abundance, interactions and various fishing and environmental variables which could affect the numbers of seabirds in attendance at vessels. In 2017/18, observers were present on 135 fishing trips spanning ~33–36°S off coastal NSW recording 3, 183 seabirds, including 10 species from seven families. The majority consisted of shearwaters (Procellariidae; 76%), albatrosses (Diomedeidae; 8%) and gulls/terns (Laridae; 10%), including several species of conservation concern. Significant seasonal variation in the abundances of the three main seabird families were recorded; however, none of the fishing or environmental variables influenced abundances of seabirds (except for the positive effect of inclement weather on shearwaters). Eleven direct interactions and a single incidence of (shearwater) bycatch were recorded in over 630 h of observed fishing (1.74 and 0.16 per 100 h fishing, respectively); these rates were likely due to the active fishing methods used which allows fisher behaviour to minimize interactions. Despite this, these rates indicate that the nearshore charter fishery does have the potential to present a threat to the conservation of seabird populations in this region. Furthermore, globally, for regions with high recreational fishing participation rates, increased and ongoing monitoring of seabird interactions with recreational fisheries is required. This study also highlights that such interactions are likely to be rare events and future monitoring may require utilization of existing broadscale recreational fisheries monitoring programmes, as well as the development of new or enhanced programmes.